2020
DOI: 10.28948/ngumuh.673508
|View full text |Cite
|
Sign up to set email alerts
|

Elma Atiklarindan Elma Si̇rkesi̇ Üreti̇mi̇ Üzeri̇ne Bi̇r Araştirma

Abstract: Elma dünya genelinde en çok tüketilen ve en çok ticareti yapılan yumuşak çekirdekli meyvelerden biri olup, taze olarak tüketilebildiği gibi elma suyu, reçel-marmelat, şarap ve sirke gibi çok çeşitli ürünlere işlenmekte ve genellikle besin içeriği bakımından zengin olan elmanın kabukları, posa ve çekirdekleri atık olarak kalmaktadır. Bu gibi tarımsal atıkların katma değeri yüksek ürünlere dönüştürülmesi, çevre sorunlarının azaltılması yanında ekonomik faydalar da sağlamaktadır. Bu çalışmada yavaş yöntem ile far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In particular, it has important metabolic effects such as inhibiting cancer cells, antimutagenic activity, reducing cardiovascular risk and lowering blood pressure (Jia et al, 2012). Studies have also shown that apple cider vinegar, which is preferred due to its richness in bioactive compound content, has antitumor effects, cholesterol regulating and reducing liver fat (Abe et al, 2007;Budak et al, 2011;Tangüler et al, 2021). Sakı apple constitutes 15% of all apple species grown in Erzincan Province.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has important metabolic effects such as inhibiting cancer cells, antimutagenic activity, reducing cardiovascular risk and lowering blood pressure (Jia et al, 2012). Studies have also shown that apple cider vinegar, which is preferred due to its richness in bioactive compound content, has antitumor effects, cholesterol regulating and reducing liver fat (Abe et al, 2007;Budak et al, 2011;Tangüler et al, 2021). Sakı apple constitutes 15% of all apple species grown in Erzincan Province.…”
Section: Introductionmentioning
confidence: 99%